Targeted pancreatic beta cell imaging for early diagnosis - Cong, Goh Zheng (2022)
Pancreatic beta cells are important in blood glucose level regulation. As type 1 and 2 diabetes are getting prevalent worldwide, we need to explore new methods for early detection of beta cell-related afflictions. Using bioimaging techniques to measure beta cell mass is crucial because a decrease in beta cell density is seen in diseases such as diabetes and thus can be a new way of diagnosis for such diseases. We also need to appraise beta cell purity in transplanted islets for type 1 diabetes patients. Sufficient amount of functional beta cells must also be determined before being transplanted to the patients. In this review, indirect imaging of beta cells will be discussed. This includes membrane protein on pancreatic beta cells whereby specific probes are designed for different imaging modalities mainly magnetic resonance imaging, positron emission tomography and fluorescence imaging. Direct imaging of insulin is also explored though probes synthesized for such function are relatively fewer. The path for successful pancreatic beta cell imaging is fraught with challenges like non-specific binding, lack of beta cell-restricted targets, the requirement of probes to cross multiple lipid layers to bind to intracellular insulin. Hence, there is an urgent need to develop new imaging techniques and innovative probing constructs in the entire imaging chain of bioengineering to provide early detection of beta cell-related pathology.